Interactive chemistry escape game as a tool of distance education: a case study of a pilot test from the first escape room - Maršálek, Roman; Trčková, Kateřina; Václavíková, Zuzana (Frontiers in Education, 2024)
The aim of this paper is to present an escape game which is the first part of a year-round, virtual, educational role-playing game built on the e-learning platform Moodle. The game is primarily focused on chemistry, although it has a great interdisciplinary overlap into physics, biology, and mathematics. The content of the game covers topics found in the chemistry curriculum at middle school and consists of a total of ten escape rooms. Each room—a separate escape game—is a self-contained unit, linked to the others by a storyline, and can be used as an educational tool even during long-term student absences, as was the case during the COVID-19 pandemic. The first room (escape game), as well as the entire year-long game, sets the mood and introduces elements of tension that reflect the story running throughout the game. The central concept is that of carbon being one of the most important elements on planet Earth. In this article, the first escape room (called Mixtures) is explained, as well as the whole overall structure of the game. The results from the pilot test conducted on 125 students are also presented. Students solved various types of tasks, and the testing showed that they performed best when describing chemical apparatus. Conversely, students were not very successful in tasks focused on chemical calculations. Teachers also shared their experiences with the escape game through a questionnaire. The teachers very positively evaluated the multidisciplinary nature of the escape game, especially the inclusion of mathematics.